КОМИЛ ИНСОН – ФУҚАРОЛИК ЖАМИЯТИНИНГ БОШ МАҚСАДИ - Матибаев, Т. (SCIENCE and SOCIETY, 2019)
In the article it is told about the social cooperation as a factor of creation of social justice and democratization of society. Society can't exist without social cooperation. The phenomenon of social justice is considered as one of laws of society with the principles of a sustainable development and social cooperation.
Keywords: social cooperation; democratic society; social justice; sustainable development; freedom; supremacy of law; civil society